Is there a suitable job for special educational need children in skill based employment - Che Mat, Hanizan; Omar, Muhd Khaizer (Human Resource Management Academic Research Society, 2022)
The Ministry of Education, Malaysia have seen vocational education as one of the important aspects that should be emphasized in Malaysia education system. Vocational and skill-based education has been further enhanced through the Malaysia Education Blueprint (2013-2025) when more children with special needs to be included in vocational and skill-based education. Prior to that, the ministry through various Malaysia Development Plans has developed four fully residential vocational schools for special need students to prepare them for a future in Technical and Vocational Education and Training. However, until today the participation of special need children in the workforce that match to their skill is still low. This qualitative study adopted two qualitative data collection method which are systematic review and interview intend to understand the job matching and employability for SEN in skill-based employment and to explore the employer perspective of hiring SEN in skill-based employment. Findings shows that special need students who graduated from the vocational schools has to compete with other mainstream school leavers in order to secure a place in the workforce. This article attempts to understand the reasons behind job-mismatch among people with disability and the employer concerns of these groups of workers.